NUMERACY LITERACY OF GRADE VII STUDENTS IN SOLVING CONTEXTUAL PROBLEMS ACROSS MATHEMATICAL ABILITY LEVELS - Hikmatul Fadhilah Sianipar; Izwita Dewi; Kms. Muhammad Amin Fauzi (Jurnal Suluh Pendidikan, 2026)
Numeracy literacy is a fundamental competency assessed through Indonesia’s Minimum Competency Assessment (AKM); however, Grade VII junior high school students’ achievement in this domain continues to exhibit significant gaps, particularly in solving contextual problems with extended narrative structures. Although numeracy literacy research in Indonesia has grown considerably, studies that simultaneously examine students’ profiles across differentiated ability levels while foregrounding the linguistic dimension as the primary explanatory variable remain scarce—especially in the local context of Stabat. To address this gap, this study investigated the numeracy literacy profile of Grade VII students at a junior high school in Stabat across three levels of mathematical ability: high, medium, and low. A descriptive qualitative approach was employed involving 20 students selected through purposive sampling. Instruments consisted of a contextual numeracy literacy test and a semi-structured interview guide. Data analysis followed the Miles and Huberman interactive model. Findings indicate that 60% of students fall within the medium ability level. More critically, the primary barrier originates from linguistic demands rather than procedural weaknesses: students demonstrate decreased accuracy when confronted with word problems exceeding three sentences, and the capacity for decoding—translating verbal context into a mathematical model—remains underdeveloped across all ability levels. The principal contribution of this study is establishing that linguistic load, not computational deficiency, is the decisive differentiating factor in numeracy literacy performance, with direct pedagogical implications: strengthening numeracy literacy cannot be decoupled from simultaneously developing students’ reading stamina and mathematical reading strategies.